Expanding the structural repertoire of beta/alpha Ant-Pro (anthranilic acid-proline) oligomers into gamma/alpha 2-Amb-Pro (2-aminomethyl benzoic acid-proline) oligomers - Ramesh, Veera V. E.; Priya, Gowri; Rajamohanan, P. R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Tetrahedron, 2012)
In this article, we report a novel class of heterogeneous synthetic oligomers featuring the conformationally constrained amino acid residues - 2-aminomethyl benzoic acid (2-Amb) and proline (Pro) in repeating sequences. Oligomers as large as hexadecamers featuring the conformationally restricted gamma/alpha 2-Amb-Pro motif have been assembled using solution-phase Boc strategy, following multi-step synthetic sequences starting from the commercially available O-toluic acid. EDC-mediated peptide coupling has been found to be optimum for the assembly of the relatively non-polar oligomers, which could be readily purified by the standard column chromatographic purification procedures. This study offers considerable prospects of expanding the structural repertoire of beta/alpha Ant-Pro motif, which has been described earlier to assume right-handed helical architecture displaying robust nine-membered-ring closed network of hydrogen-bonding interactions, into gamma/alpha 2-Amb-Pro motif. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Amino acids; Foldamer; Peptides; Proline; Synthetic oligomers

Foldamers: they're not just for biomedical applications anymore - Prabhakaran, Panchami; Priya, Gowri; Sanjayan, Gangadhar J. (Angewandte Chemie-International Edition, 2012)
Keywords: Foldamers; foldaxanes; molecular shuttles; nanotechnology

Helical folding in heterogeneous foldamers without inter-residual backbone hydrogen-bonding - Priya, Gowri; Kotmale, Amol S.; Gawade, Rupesh L.; Mishra, Deepti; Pal, Sourav; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Chemical Communications, 2012)
This communication describes a set of hybrid foldamers that do not feature inter-residual, but intra-residual backbone hydrogen-bonding, yet adopt a preferentially folded conformation displaying right-handed helical architecture. Conformational ordering is apparently due to the combined conformational restrictions imposed by the conformationally restricted individual amino acid residues with which the oligomers are made of.

Multifaceted folding in a foldamer featuring highly cooperative folds - Ramesh, Veera V. E.; Priya, Gowri; Kotmale, Amol S.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Chemical Communications, 2012)
Herein, we report on the folding pattern observed in a synthetic peptide featuring two highly mutually dependent, yet strikingly dissimilar, closed networks of hydrogen-bonded rings that work in a cumulative fashion to stabilize the entire folded architecture of the peptide. Structural studies unequivocally suggest that disruption of any one of these mutually-dependent hydrogen-bonded networks is deleterious to the stability of the fully folded conformation of the peptide.

Orthanilic acid-promoted reverse turn formation in peptides - Kale, Sangram S.; Priya, Gowri; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Chemical Communications, 2013)
Orthanilic acid (2-aminobenzenesulfonic acid, (S)Ant), an aromatic beta-amino acid, has been shown to be highly useful in inducing a folded conformation in peptides. When incorporated into peptide sequences (Xaa-(S)Ant-Yaa), this rigid aromatic beta-amino acid strongly imparts a reverse-turn conformation to the peptide backbone, featuring robust 11-membered-ring hydrogen-bonding.

Conformational modulation of peptides using beta-amino benzenesulfonic acid ((S)Ant) - Priya, Gowri; Kotmale, Amol S.; Chakravarty, Debamitra K.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2015)
This communication describes the utility of a conformationally restricted aromatic beta-amino acid (2-aminobenzenesulfonic acid, (S)Ant) inducing various folding interactions in short peptides. Sandwiching (S)Ant between diverse amino acid residues was shown to form robust folded architectures featuring a variety of H-bonded networks, suggesting its utility in inducing peptide folding.